Medical magnesium alloy with biological catalytic composite coating as well as preparation and application of medical magnesium alloy
By constructing a biocatalytic composite coating on the surface of a magnesium-based metal matrix, combining the covalent grafting technology of Schiff alkali and MOFs materials, the corrosion problem of magnesium alloy in the human body is solved, and the biocatalytic function is realized, which significantly improves the implanted material stability and biocompatibility.
Patent Information
- Application Number
- CN202411334207.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-01-07
AI Technical Summary
The rapid corrosion of magnesium alloys in the human body leads to adverse reactions, and the prior art is difficult to effectively control its corrosion rate and realize biocatalytic functions.
The biocatalytic composite coating is constructed on the surface of the magnesium-based metal matrix, including the modified functional organic molecule NH4TiOF3 layer and the outer coating are covalently grafted by Schiff base guest molecules and chelated metal ions to form the MOFs material UiO- 66-NH2, UiO-66-COOH or UiO-66-OH realizes corrosion-proof and biocatalytic functions.
This composite coating can not only effectively prevent corrosion of magnesium alloys, but also catalyze biochemical reactions in the human body, such as releasing NO, decomposing hydrogen peroxide and inhibiting lipid peroxidation, reducing the risk of postoperative inflammation, and showing good biocompatibility and long-term stability.
Smart Images

Figure CN119258269A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of biomedical materials, and more specifically, relates to a medical magnesium alloy with a biocatalytic composite coating and its preparation and application, which can be used as a supporting material for human body implantation. Background Art
[0002] Magnesium is widely considered to be a potentially revolutionary orthopedic biomaterial due to its biodegradable metal, good biocompatibility and ideal Young's modulus close to that of natural cortical bone. Magnesium and its alloys have higher strength relative to natural bone, but their Young's modulus is very close to that of cortical bone, which means that it has unique properties in reducing stress shielding during load transfer at the implant-bone interface. Therefore, these properties overcome the shortcomings of traditional metal and synthetic polymer orthopedic devices, making them more suitable candidates for the treatment of challenging bone diseases.
[0003] As a medical implant material, magnesium has many advantages and a good prospect for application. However, due to its high electronegativity in the human body, the rapid corrosion behavior of magnesium alloys in the early stage of implantation will produce many adverse reactions, such as enrichment of magnesium ions, local alkalization and corrosion byproducts, leading to bone dissolution, bubble aggregation, and gap formation between implants and tissues. At present, the main strategies for controlling magnesium-based corrosion mainly include surface coating method and alloy method. Constructing a high-quality surface coating that can control the corrosion rate will be a good solution to the problem.
[0004] Metal-Organic Frameworks (MOFs) materials are a type of zeolite-like materials with a periodic network structure formed by self-assembly of multidentate organic ligands containing oxygen, nitrogen, etc. and metal ions. MOFs also have the properties of high crystallinity, porosity, and strong metal-ligand interactions. These properties also give MOFs some characteristics, such as high specific surface area, high porosity, and enhanced chemical and thermal stability due to the presence of strong coordination bonds. It is precisely because of these characteristics that MOFs have become a new type of multifunctional material. In the field of anti-corrosion coating materials, many studies have used MOFs as coating materials in the field of anti-corrosion coating materials to achieve the purpose of resisting corrosion.
[0005] Taking the inventor's previous Chinese patent application CN114191610A as an example, the magnesium-based multifunctional composite active coating obtained is "NH 4 TiOF 3"Coating + functional organic molecule layer + MOFs coating", specifically including a magnesium-based substrate and a composite active coating on at least one surface of the magnesium-based substrate; the composite active coating is an ammonium trifluorotitanate active coating and a metal organic framework active coating from the surface of the magnesium-based substrate in sequence to the outside; a functional organic molecule layer is also included between the ammonium trifluorotitanate active coating and the metal organic framework active coating, and the functional organic molecule layer is used to improve the heterogeneous nucleation of the metal organic framework grains on the surface of the ammonium trifluorotitanate layer. Although the MOFs membrane coating with dense structure and strong adhesion constructed on the surface of the substrate obtained by the prior art can construct a MOFs membrane coating with dense structure and strong adhesion on the surface of the substrate, it does not involve any biocatalytic effect.
[0006] Schiff base refers to a class of organic compounds containing imine or azomethine characteristic groups (-RC=N-), which are usually formed by a series of reactions of active carbonyl and amine compounds. Since the elements N, O, S, etc. contained in its structure have strong coordination, Schiff base can be used as a ligand to chelate most metal ions. Although there are related reports in the prior art on the use of Schiff base reaction to generate catalytic materials, the Schiff bases they use are often used as solid chelating agents, and the catalytic materials as the main body are often biologically toxic, and are mostly used for industrial catalysis, and cannot be used for organisms.
[0007] Most metals play a vital role in the human body. Most biochemical reactions in the human body require the participation of various metal ions. For example, the decomposition of hydrogen peroxide in the human body. Since some metal ions have strong reducibility, they can catalyze their decomposition to produce oxygen and water, realizing autocatalysis in the body. However, if a metal organic framework structure centered on these metals is directly constructed on the surface of the substrate, the original substrate supporting metal will corrode rapidly, and the stability is worrying. Taking Comparative Example 1 as an example, Comparative Example 1 is to directly construct a MOFs structure centered on Cu on the magnesium-based surface (HKUST-1). Cu and the substrate magnesium metal form electrochemical corrosion, which accelerates the decomposition of the substrate. Summary of the invention
[0008] In view of the above defects or improvement needs of the prior art, the purpose of the present invention is to provide a medical magnesium alloy with a biocatalytic composite coating and its preparation and application, wherein the composition and structure of the composite coating on the surface of the magnesium-based metal substrate are improved, and in the "NH 4 TiOF 3 On the basis of the existing achievement of "coating + functional organic molecule layer + MOFs coating", a composite coating with both anti-corrosion and biocatalytic functions is obtained by covalently grafting Schiff base guest molecules on the outer surface of the MOFs coating and chelating metal ions.
[0009] To achieve the above object, according to one aspect of the present invention, a medical magnesium-based metal material with a biocatalytic composite coating is provided, characterized in that it is obtained by forming an inner coating and an outer coating from the inside to the outside on a magnesium-based metal substrate using pure magnesium or a magnesium alloy as the magnesium-based metal substrate, wherein:
[0010] The inner coating is modified with NH 4 TiOF 3 The layer has a corrosion protection function; the functional organic molecules are silane molecules;
[0011] The outer coating is constructed by covalently grafting Schiff base guest molecules on the outer surface of the MOFs material and chelating metal ions, and has a catalytic function; wherein the MOFs material is UiO-66-NH 2 , UiO-66-COOH or UiO-66-OH; the metal ion is Cu 2+ 、Zn 2+ , Fe 2+ or Fe 3+ At least one of .
[0012] As a further preferred embodiment of the present invention, NH 4 TiOF 3 The thickness of the layer is 10 to 20 μm;
[0013] The thickness of the MOFs material in the outer coating layer is 10-20 μm.
[0014] As a further preferred embodiment of the present invention, the Schiff base guest molecule is 2,5-dihydroxybenzaldehyde or pyridine-2-carboxaldehyde.
[0015] As a further preferred embodiment of the present invention, the magnesium-based metal matrix is pure magnesium, AZ31 magnesium alloy or WE43 magnesium alloy.
[0016] As a further preferred embodiment of the present invention, the aminosilane molecule is specifically 3-aminopropyltriethoxysilane (APTES).
[0017] According to another aspect of the present invention, the present invention provides a method for preparing the above-mentioned medical magnesium-based metal material with a biocatalytic composite coating, characterized in that it comprises the following steps:
[0018] (1) Preparation of NH on the surface of magnesium-based metal matrix by hydrothermal reaction 4 TiOF 3 Active coating;
[0019] (2) Using the soaking method, functional organic molecules are modified with NH 4 TiOF3 Active coating;
[0020] (3) In the case of NH modified with functional organic molecules 4 TiOF 3 Continue to construct a metal organic framework active coating on the active coating;
[0021] (4) covalently grafting Schiff base guest molecules onto the surface of the metal organic framework by heating and stirring under a protective gas atmosphere;
[0022] (5) Chelating metal ions by immersion reaction method.
[0023] As a further preferred embodiment of the present invention, step (4) is to first add the product obtained in step (3) to an organic solvent, and then add a Schiff base guest molecule thereto under a protective gas atmosphere, stirring and heating to react for 12 to 24 hours; wherein the volume ratio of the Schiff base guest molecule to the organic solvent is 1:50 to 1:20; the heating temperature is 40°C to 70°C; and the reaction time is 12 to 24 hours.
[0024] The protective gas is preferably N 2 .
[0025] As a further preferred embodiment of the present invention, step (5) is to first disperse the metal ion source material in an organic solvent to obtain a metal ion solution, and then soak the product obtained in step (4) in the metal ion solution for 12 to 24 hours; wherein the concentration of the metal ion solution is 0.5M to 1M;
[0026] The metal ion source material is anhydrous cupric acetate, zinc chloride, ferric chloride, ferrous chloride or cupric chloride.
[0027] According to another aspect of the present invention, the present invention provides the use of the above-mentioned medical magnesium-based metal material with a biocatalytic composite coating in the preparation of medical implant materials.
[0028] Through the above technical scheme conceived by the present invention, compared with the prior art, the present invention utilizes the surface functional group characteristics of MOFs to form a Schiff base structure with guest molecules, thereby realizing the construction of a multifunctional platform for implant material corrosion protection and biocatalysis. The present invention constructs a biocatalytic composite coating based on MOFs functional materials on a magnesium-based metal matrix, and the composite coating includes an inner coating and an outer coating, wherein the inner coating is NH modified with functional organic molecules. 4 TiOF 3The outer layer and outer coating are constructed by covalently grafting the MOFs material with Schiff base chelated metal ions. The corresponding medical magnesium-based metal material with biocatalytic composite coating can utilize the metal active center on the outermost surface of the coating to catalyze biochemical reactions in the body and realize biological multifunctionality. The composite coating has multifunctional characteristics, which can not only realize corrosion protection, but also provide biocatalytic functions. When the magnesium-based metal material with composite coating is implanted into the human body, the metal ion active center chelated on its catalytic surface can catalyze the reaction of endogenous substance GSNO in the human body to release NO, which helps vasodilation; or realize the function similar to catalase, effectively catalyzing the decomposition of excess hydrogen peroxide in the body; when oxidative stress occurs at the implantation site, it can also effectively catalyze the decomposition of lipid peroxidation substances such as superoxide anions and hydroxyl free radicals to reduce lipid peroxidation.
[0029] The composite coating of the present invention comprises NH 4 TiOF 3 Inner coating and catalytic MOFs covalently grafted with Schiff base to chelate Zn 2+ , Cu 2+ , Fe 2+ , Fe 3+ Medical magnesium materials are often used in bone repair and heart stents, and are often accompanied by inflammation or the risk of elevated indicators after surgery. The composite coating of the present invention can reduce the risk of elevated biochemical indicators after surgery on the basis of the original material protection, and can alleviate the problem of postoperative medication to a certain extent. For example, when the chelated metal ion is Cu 2+ When the chelated metal ion is Zn 2+ When the metal ion is Fe 2+ When the metal ion is Fe 3+ Due to its strong redox activity and multi-catalytic properties, it can be used as an electrochemical sensor in vivo. 2 For example, when the outer coating is UiO-66-NH 2 Covalent grafting of Schiff base to chelate Cu 2+ When the outer coating is UiO-66-NH 2 Covalent grafting of Schiff base to chelate Zn 2+ When the outer coating is UiO-66-NH 2 Covalent grafting of Schiff base to chelate Fe2+ When the implant material is implanted into the human body, due to the inflammation and stress response after the implantation, some indicators in the body increase. The chelated guest metal ions act as directional catalytic sites, catalyzing the release of NO and the reduction of ROS (reactive oxygen) in the human body.
[0030] The present invention utilizes the guest metal ions chelated by the composite coating as directional catalytic sites to achieve the construction of a multifunctional platform for corrosion protection and biocatalysis. Considering the corrosion protection requirements of magnesium-based metal matrix implants, some corrosion protection coatings have been reported in the prior art, but technicians often do not think of applying additional metal ions to the outermost layer of the coating (because if so, the outermost metal ions will lose the protection of the coating, and additional subsequent treatment of the coating often poses a risk of damaging the corrosion protection performance of the original corrosion protection coating). The present invention overcomes this technical prejudice and, in addition to the previously reported "NH 4 TiOF 3 On the basis of "coating + functional organic molecule layer + MOFs coating", the metal ions are further chelated by Schiff base outside the MOFs layer. In the biological environment (such as in the human body), these newly introduced metal ions can serve as the core to achieve the in vivo catalytic performance of the implanted human body material (such as the effective catalytic release of NO in the human body, the catalytic decomposition of hydrogen peroxide, the effective catalytic decomposition of lipid peroxidation factors, etc.), which is equivalent to constructing a multifunctional biocatalytic platform on the surface of the composite coating, and it also has good long-term stability and will not destroy the anti-corrosion performance of the original coating. The present invention effectively constructs a biological multifunctional catalytic platform, which can meet the complex clinical reactions in the human body, has excellent biocompatibility, and is non-toxic and harmless when implanted in the human body.
[0031] The composite coating of the present invention is a multifunctional catalytic platform MOFs composite material. 4 TiOF 3 On the basis of the metal organic framework catalytic coating, the catalytic surface is constructed by continuing Schiff alkalization to chelate zinc, copper, iron and other ions on the outer surface of the MOFs material. Specifically, the present invention can achieve the following beneficial effects:
[0032] (1) The present invention constructs a composite coating with biocatalysis based on MOFs functional materials, uses Schiff guest molecules to react with MOFs themselves to produce Schiff bases, and chelates different metal ions as a nanocoating. The obtained biocomposite coating has the dual functions of corrosion protection and biocatalysis, and is applied to human implant support materials and can catalyze biochemical reactions in vivo.
[0033] When the metal material is implanted in the human body, the multifunctional coating can respond to changes in environmental indicators in the human body: on the one hand, when the molecular weight of NO in the human body is too low, the metal organic framework coating contacts the RSNO medium, catalyzing the production of NO molecules to promote vasodilation; it can achieve the self-catalytic release of NO in the human body. On the other hand, when the ROS in the human body is too high, it can effectively catalyze and inhibit ROS influencing factors, thereby achieving the regulation of the level of oxidative stress in the human body.
[0034] (2) The composite coating of the present invention utilizes MOFs to covalently graft Schiff base to chelate Zn 2+ , Cu 2+ , Fe 2+ , Fe 3+ The metal organic framework composite material constructed by the catalyst has a rich selection of Schiff guest molecules and catalytic center ions, which can be used for catalytic reaction processes in different organisms. 2+ When the GSNO in the human body undergoes a redox reaction, it decomposes into NO, thus realizing the self-catalytic release of NO in the human body; the catalytic center is Fe 2+ When the lipid peroxidation is inhibited, the excess hydrogen peroxide in the human body will undergo a redox reaction with it, and the free radicals generated in the process will be catalytically inhibited, thereby achieving the inhibition of lipid peroxidation in the human body.
[0035] (3) The present invention utilizes an inner coating and an outer coating to construct a composite coating, and the coating has good mechanical properties and excellent corrosion resistance. Its corrosion resistance can still be maintained after 90 days, and it has excellent biocatalytic performance.
[0036] (4) The chelated metal catalytic central ion of the present invention has excellent biological antibacterial properties, and its antibacterial effect can still be maintained after 14 days of simulated immersion in vitro.
[0037] (5) The raw materials for preparing the composite coating of the present invention are readily available, and the NH 4 F, TBOT, APTES, zirconium chloride, 2-aminoterephthalic acid, etc. are examples. They can all be purchased directly on the market, are easy to obtain, and are very convenient for medical production and preparation.
[0038] Due to the high activity of the magnesium substrate, each increase in the material preparation process will increase the risk of substrate corrosion. Based on the original protective coating, the present invention creatively uses the Schiff base structure to chelate the metal central ion instead of directly constructing a MOFs structure centered on the catalytic metal ion. As shown in the examples below, the problem of electrochemical self-corrosion of the substrate is effectively avoided while retaining the biocatalytic function of the original design. While increasing the process steps, the substrate corrosion problem is solved and long-term corrosion protection verification is achieved.
[0039] The Schiff base structure of the present invention is constructed on the basis of the original MOFs. As shown in Comparative Example 1 below, if a metal organic framework material (HKUST-1) centered on Cu is constructed, it is found that it will accelerate the electrochemical self-corrosion of the substrate. The present invention selects a Zr-based metal organic framework material with stronger protective performance (i.e., UiO-66-NH 2 , UiO-66-COOH, UiO-66-OH), and creatively used Schiff base guest molecules (e.g., 2,5-dihydroxybenzaldehyde, pyridine-2-carboxaldehyde) to chelate Cu 2+ 、Zn 2+ , Fe 2+ The metal catalytic central ions including etc. were finally obtained into medical magnesium-based metal materials with biocatalytic composite coating, which effectively overcame the problem of substrate corrosion.
[0040] In summary, the present invention achieves the efficient unification of support, protection and functionality of human implant materials, and has excellent performance in mechanical stress, controllable corrosion, biocatalysis, biocompatibility and antibacterial ability, and can realize implant repair functions in many aspects and dimensions. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] Figure 1 The metal organic framework composite material (UiO-66-NH 2 )Scanning electron microscope image.
[0042] Figure 2 This is a scanning electron microscope image of the Schiff base grafted metal organic framework composite material (UiO-66-Pyr) prepared in step 4 of Example 1.
[0043] Figure 3 This is a scanning electron micrograph of the metal organic framework composite material (UiO-66-Pyr-Cu) obtained in step 5 of Example 1 after Schiff alkalization and chelation of metal ions.
[0044] Figure 4 NTiF and UiO-66-NH obtained in different steps of Example 1 2 , UiO-66-Pyr, and UiO-66-Pyr-Cu samples in 0.9wt% NaCl solution; the inset in the figure is the EIS graph of pure magnesium itself in 0.9wt% NaCl solution.
[0045] Figure 5 NTiF and UiO-66-NH obtained in different steps of Example 1 2Comparison of pH changes of UiO-66-Pyr and UiO-66-Pyr-Cu samples in 0.9wt% NaCl solution over 90 days.
[0046] Figure 6 UiO-66-NH obtained in different steps of Example 1 2 Comparison of NO release rates catalyzed by UiO-66-Pyr, and UiO-66-Pyr-Cu samples to generate NO.
[0047] Figure 7 UiO-66-NH obtained in different steps of Example 1 2 , UiO-66-Pyr, and UiO-66-Pyr-Cu samples at different H 2 O 2 Comparison of fluorescence spectra of catalytic decomposition of hydrogen peroxide under participating conditions.
[0048] Figure 8 The in vitro antibacterial properties of UiO-66-Pyr and UiO-66-Pyr-Cu samples obtained in different steps of Example 1 and the comparison chart after 14 days of culture. DETAILED DESCRIPTION
[0049] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.
[0050] The MOFs layer in the composite coating of the present invention can be uniformly coated on the surface of the substrate by a solvent thermal method, spin coating or blade coating. Taking the solvent thermal method as an example, the preparation method of the composite coating of the present invention may include the following steps:
[0051] (1) Preparation of NH on magnesium-based surfaces by hydrothermal reaction 4 TiOF 3 Active coating;
[0052] (2) Using the soaking method, functional organic molecules are modified with NH 4 TiOF 3 Active coating;
[0053] (3) Using the solvothermal method to construct metal organic framework active coatings on the surface of functional organic molecules;
[0054] (4) Adopt N 2 Schiff base guest molecules are covalently grafted onto the surface of the metal organic framework by heating and stirring under atmosphere;
[0055] (5) using an immersion reaction method to chelate metal ions;
[0056] Wherein, step (1) is to fully mix the ammonium fluoride solution and the hydrogen fluoride solution, add them to the organic solvent, then add the titanium source (e.g., tetraisopropyl titanate), then add magnesium to the reaction kettle, seal it and perform the solvent thermal reaction, so as to obtain the intermediate product A: NH 4 TiOF 3 coating;
[0057] Step (2) is to fully mix the functional polymer (e.g., aminosilane molecules) with water and an organic solvent, stir for 0.5 to 1 hour, then add the intermediate product A obtained in step (1) and soak to allow the functional polymer to fully modify the NH 4 TiOF 3 Coating, that is, obtaining intermediate product B;
[0058] Step (3) is to fully dissolve the metal ions (e.g., zirconium ions) and organic ligands (e.g., 2-aminoterephthalic acid) in an organic solvent, add the intermediate product B of step (2) into a reaction kettle, seal it and perform a solvent thermal reaction to obtain the intermediate product C; the metal ions and organic ligands used in this step can construct a MOFs layer;
[0059] Step (4) is to place the intermediate product C obtained in step (3) in an organic solvent, and then 2 Add a Schiff base guest molecule (e.g., pyridine-2-carboxaldehyde) into the atmosphere, stir and heat for 12 to 24 hours to obtain the intermediate product D;
[0060] Step (5) is to introduce a metal ion source material (such as anhydrous copper acetate, zinc chloride, ferric chloride, ferrous chloride or cupric chloride) into an organic solvent, and place the intermediate product D obtained in step (4) in the solution for immersion for 12 to 24 hours to obtain a MOFs-based biocatalytic composite coating.
[0061] The organic solvent can be ethanol, DMF or methanol solution.
[0062] Of course, in addition to using the solvothermal method to generate the MOFs layer on the substrate, it can also be achieved by spin coating or scraping (for example, refer to the prior art Chinese patent application CN202310434791.8).
[0063] The following are specific embodiments:
[0064] Example 1
[0065] A method for constructing a biocatalytic composite coating based on MOFs comprises the following steps:
[0066] (1) Preparation of NH on magnesium-based surfaces by hydrothermal reaction 4 TiOF 3 First, the surface of the pure magnesium cylinder (cylinder diameter is 14 mm, thickness is 4 mm) was polished with 400#, 1000#, and 2000# sandpapers respectively, and then ultrasonically cleaned in ethanol and acetone in turn, and dried for use. 4 F aqueous solution, take 250 μL of the prepared NH 4 The F solution and 300 μL 40% HF solution were added to 15 mL anhydrous ethanol and mixed thoroughly under magnetic stirring for 10 min. Then 500 μL tetraisopropyl titanate (TBOT) was added and magnetic stirring was continued for 15 min. After TBOT was fully hydrolyzed, the mixture was placed in a 50 mL polytetrafluoroethylene reactor with the surface-treated magnesium-based material for hydrothermal reaction at 140 °C for 6 h. After cooling to room temperature, the sample was taken out and rinsed with ethanol and acetone, respectively, and dried for use to obtain NH 4 TiOF 3 The coating was then coated and the obtained sample was recorded as NTiF.
[0067] (2) Modify the sample surface with 3-aminopropyltriethoxysilane (APTES) to improve the heterogeneous nucleation of MOFs crystals on its surface. Add 1 mL of deionized water to 18 mL of ethanol and stir to mix thoroughly. Add 1 mL of 3-aminopropyltriethoxysilane (APTES) and stir magnetically for 1 h. After APTES is fully hydrolyzed, add the obtained NH 4 TiOF 3 The coating was placed in a 50 mL polytetrafluoroethylene reactor liner and allowed to soak for 1 hour. The sample was then taken out and rinsed with ethanol and acetone, respectively, and dried for later use.
[0068] (3) 0.121 g zirconium chloride, 0.091 g 2-aminoterephthalic acid and 10 μL deionized water were added to 20 mL N,N-dimethylformamide (DMF) and fully ultrasonically dissolved and mixed with the modified NH 4 TiOF 3 The coating samples were introduced into a 50 mL polytetrafluoroethylene reactor for hydrothermal reaction at 120 °C for 24 h. After cooling to room temperature, the samples were taken out and rinsed with DMF, ethanol, and acetone, respectively, and dried for standby use to obtain a composite coating. The obtained sample was recorded as UiO-66-NH 2 Its SEM is as follows Figure 1 shown.
[0069] (4) Place the sample prepared in step (3) in 20 mL of N,N-dimethylformamide (DMF) and 2After blowing for 15 min, 300 μL of pyridine-2-carboxaldehyde and N 2 The reaction was carried out at 40°C for 24 hours, and the sample was taken out and rinsed with DMF, ethanol and acetone respectively, and dried for use to obtain a Schiff base grafted product, which was recorded as UiO-66-Pyr. Figure 2 shown.
[0070] (5) The sample in step (4) was immersed in a 0.5M anhydrous copper acetate solution, the solvent being N,N-dimethylformamide (DMF), for 12 hours, and then the sample was taken out and rinsed with DMF, ethanol, and acetone, respectively, and dried for use to obtain a biocatalytic composite coating based on MOFs. The obtained sample was recorded as UiO-66-Pyr-Cu. Its SEM is as follows Figure 3 shown.
[0071] (6) The sample in step (4) was immersed in a 0.5 M zinc chloride solution, the solvent being N,N-dimethylformamide (DMF), for 12 h, and then the sample was taken out and rinsed with DMF, ethanol, and acetone, respectively, and dried for use to obtain a MOFs-based biocatalytic composite coating. The obtained sample was recorded as UiO-66-Pyr-Zn.
[0072] (7) The sample in step (4) was immersed in a 0.5 M ferrous chloride solution, the solvent being N,N-dimethylformamide (DMF), for 12 h, and then the sample was taken out and rinsed with DMF, ethanol, and acetone, respectively, and dried for use to obtain a MOFs-based biocatalytic composite coating. The obtained sample was recorded as UiO-66-Pyr-Fe(Ⅱ).
[0073] The pure magnesium cylinder used in step (1) and the samples NTiF, UiO-66-NH 2 The EIS comparison experiment of UiO-66-Pyr and UiO-66-Pyr-Cu in 0.9wt% NaCl solution shows that Figure 4 As shown in the figure, it can be seen that the capacitance arc radius of (UiO-66-Pyr-Cu) after Schiff base grafting and chelating metal ions is significantly larger than that of pure magnesium and MOFs coating, indicating that the addition of metal organic framework composite materials can effectively improve the corrosion resistance of the coating.
[0074] At the same time, the medical magnesium-based metal material with biocatalytic composite coating obtained by the present invention has good structural stability and long-term effectiveness. The pure magnesium cylinder used in step (1) and the samples NTiF, UiO-66-NH 2Long-term in vitro immersion experiments were conducted on UiO-66-Pyr and UiO-66-Pyr-Cu in 0.9wt% NaCl solution. The immersion solution was changed every 10 days, and the pH changes of the solution after corrosion were recorded. Figure 5 It can be seen from the figure that after the Schiff base is grafted and the metal ions are chelated, the pH change of (UiO-66-Pyr-Cu) is the smallest and can be stabilized below 8. However, due to the self-corrosion of pure magnesium, the pH of the solution increases rapidly, indicating that the addition of metal-organic framework composites can effectively improve the corrosion resistance of the coating.
[0075] Example 2
[0076] An application of a biocatalytic composite coating based on MOFs comprises the following steps:
[0077] (1) UiO-66-NH obtained in different steps of Example 1 2 , UiO-66-Pyr, and UiO-66-Pyr-Cu samples. The back and sides of the samples were encapsulated with resin, leaving only the treated surface exposed. A 65 μM GSNO solution was prepared as the reaction base solution. The Elabscience nitric oxide (NO) colorimetric test kit was used to detect the ability of the samples to catalyze NO release. Specifically, the samples were placed in a 24-well plate, and three parallel samples were set for each sample. 500 μL of GSNO base solution was added, and then reagents were added according to the kit method. 160 μL of the supernatant was taken and the OD value was measured at 550 nm on an ELISA reader. The results are shown as follows: Figure 6 shown.
[0078] (2) UiO-66-NH obtained in different steps of Example 1 2 For the samples of UiO-66-Pyr and UiO-66-Pyr-Cu, the back and sides of the samples were encapsulated with resin, leaving only the treated surface exposed. The samples were placed in a 24-well plate, and three parallel samples were set for each sample. 0.5 mM H 2 O 2 After reacting with the sample for 5 minutes, 0.5 mM terephthalic acid (PTA) was added as a hydroxyl radical scavenger for 5 minutes. The supernatant was then measured for fluorescence intensity at 435 nm using a fluorescence spectrophotometer. The results are as follows: Figure 7 shown.
[0079] (3) UiO-66-NH obtained in different steps of Example 1 2The back and sides of the samples were sealed with resin, leaving only the treated surface exposed. The samples were placed in a 24-well plate, and three parallel samples were set for each sample. Superoxide anion (O) was evaluated using a superoxide anion assay kit (Nanjing Jianshe Bioengineering Institute, Nanjing, China) according to the manufacturer's instructions. 2- ) scavenging activity. After standing for 10 minutes, 100 μL of the clear solution was taken and the OD value was measured at 550 nm by an ELISA instrument. The results are shown in Table 1. It is not difficult to see that the UiO-66-Pyr-Cu sample has the best catalytic performance and can catalytically inhibit more than 56.3% of superoxide anions.
[0080] Table 1: Comparison of the inhibition rates of superoxide anions and hydroxyl radicals of different samples
[0081]
[0082] (4) UiO-66-NH obtained in different steps of Example 1 2 For the samples of UiO-66-Pyr and UiO-66-Pyr-Cu, the back and sides of the samples were encapsulated with resin, leaving only the treated surface exposed. The samples were placed in a 24-well plate, and three parallel samples were set for each sample. 0.5 mM H 2 O 2 and 0.5 mM FeSO 4 The Fenton reaction was generated for 1.5 min. Then, the solution was added to the well plate and incubated with the sample for another 1.5 min to eliminate ·OH. Finally, 0.3×10 -4 M salicylic acid (SA) was used to detect the residual ·OH. SA was oxidized by ·OH to 2,3-dihydroxybenzoic acid to obtain a purple product. The ·OH removal rate was calculated by the absorbance obtained at 510 nm by UV-visible absorption spectroscopy. The results are shown in Table 1, from which it is not difficult to see that the UiO-66-Pyr-Cu sample has the best catalytic performance and can catalytically inhibit more than 57.5% of ·OH.
[0083] Example 3
[0084] An application of a biocatalytic composite coating based on MOFs comprises the following steps:
[0085] (1) For the UiO-66-Pyr and UiO-66-Pyr-Cu samples obtained in different steps of Example 1, the samples were sealed with silicone rubber, only the test surface was exposed, and they were placed in disposable culture dishes according to the groups, and sterilized by irradiation of both sides under ultraviolet light for 30 min respectively, and then set aside. Cover film treatment: The cover film was cut into a circle with a diameter of 10 mm, soaked in alcohol for 1 hour, and then dried for later use.
[0086] (2) Take three 12 mL bacterial culture tubes, add 3 mL of LB liquid medium to each tube, pick a single colony from the solid culture medium of Staphylococcus aureus and Escherichia coli and add it to the liquid culture medium, and use the other tube as a blank control. Place the tube in a constant temperature shaker (37°C, 200 rpm) and shake culture overnight (15 h).
[0087] (3) Centrifuge the overnight culture, resuspend in sterile PBS solution, and then dilute the culture to 10 6 CFU / mL, add 50μL of diluted bacterial solution to the sample test surface, pick up the sterilized cover film with sterile tweezers and cover the sample respectively, make sure to flatten it, make the bacteria evenly contact the sample, and the bacterial solution should not exceed the edge of the cover film; the control group is a group without sample. Place it in a 37℃ constant temperature incubator and culture it for 24h. After the culture is completed, add 5mL of sterile PBS to the culture dish to fully wash out the bacterial solution. Use sterile PBS solution to dilute the eluate 10 times continuously, take 100μL of the dilution and evenly spread it on the LB solid culture medium. Place it in a 37℃ constant temperature incubator for 18h, take it out, take pictures and record the colonies.
[0088] The results are as follows Figure 8 As shown in the figure, the obtained sample UiO-66-Pyr has slightly poor antibacterial activity against Escherichia coli, while UiO-66-Pyr-Cu has excellent antibacterial activity against Escherichia coli and Staphylococcus aureus, with an antibacterial activity of more than 99%. The final sample can still maintain good antibacterial activity against the two bacteria after being immersed in the simulated fluid in vitro for 14 days, which proves the long-term antibacterial activity of the final coating and provides a long-term sterile environment for the implantation site.
[0089] Comparative Example 1
[0090] Referring to steps (1) and (2) of Example 1, the modified NH 4 TiOF 3 Coating sample; then, 1.86g of copper nitrate pentahydrate and 1.2596g of 1,3,5-benzenetricarboxylic acid were added to 20mL of N,N-dimethylformamide (DMF), and after being fully dissolved by ultrasonic, the modified NH 4 TiOF 3 The coating samples were introduced into a 50 mL polytetrafluoroethylene reactor for hydrothermal reaction at 110 °C for 18 h. After cooling to room temperature, the samples were taken out, rinsed with DMF, ethanol, and acetone, and dried for use to obtain a composite coating. The obtained sample was recorded as NTiF / HKUST-1.
[0091] The comparative sample was immersed in 0.9wt% NaCl solution for a long time in vitro. The immersion solution was changed every 10 days. It was found that the amount of hydrogen released by the sample after 3 days of immersion was greater than the total amount of hydrogen released by pure magnesium in 3 days. The failure reason was that Cu 2+ Electrochemical corrosion with Mg accelerates the corrosion process of the substrate, leading to material failure.
[0092] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A medical magnesium-based metal material with a biocatalytic composite coating, characterized in that: It is obtained by using pure magnesium or magnesium alloy as a magnesium-based metal matrix and forming an inner coating and an outer coating from the inside to the outside on the magnesium-based metal matrix, wherein: The inner coating is a NH4TiOF3 layer modified with functional organic molecules, which has a corrosion protection function; the functional organic molecules are silane molecules; The outer coating is constructed by covalently grafting Schiff base guest molecules on the outer surface of the MOFs material and chelating metal ions, and has a catalytic function; wherein the MOFs material is UiO-66-NH2, UiO-66-COOH or UiO-66-OH; the metal ions are Cu 2+ 、Zn 2+ , Fe 2+ or Fe 3+ At least one of .
2. The medical magnesium-based metal material with a biocatalytic composite coating as claimed in claim 1, characterized in that: The thickness of the NH4TiOF3 layer in the inner coating is 10 to 20 μm; The thickness of the MOFs material in the outer coating layer is 10-20 μm.
3. The medical magnesium-based metal material with a biocatalytic composite coating as claimed in claim 1, characterized in that: The Schiff base guest molecule is 2,5-dihydroxybenzaldehyde or pyridine-2-carboxaldehyde.
4. The medical magnesium-based metal material with a biocatalytic composite coating as claimed in claim 1, characterized in that: The magnesium-based metal matrix is pure magnesium, AZ31 magnesium alloy or WE43 magnesium alloy.
5. The medical magnesium-based metal material with a biocatalytic composite coating as claimed in claim 1, characterized in that: The aminosilane molecule is specifically 3-aminopropyltriethoxysilane (APTES).
6. The method for preparing the medical magnesium-based metal material with a biocatalytic composite coating according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) A NH4TiOF3 active coating was prepared on the surface of a magnesium-based metal substrate by a hydrothermal reaction method; (2) using an immersion method to modify the NH4TiOF3 active coating with functional organic molecules; (3) Continuing to construct a metal organic framework active coating on the NH4TiOF3 active coating modified with functional organic molecules; (4) covalently grafting Schiff base guest molecules onto the surface of the metal organic framework by heating and stirring under a protective gas atmosphere; (5) Chelating metal ions by immersion reaction method.
7. The preparation method according to claim 6, characterized in that: Step (4) is to first add the product obtained in step (3) to an organic solvent, and then add a Schiff base guest molecule thereto under a protective gas atmosphere, stirring and heating to react for 12 to 24 hours; wherein the volume ratio of the Schiff base guest molecule to the organic solvent is 1:50 to 1:20; the heating temperature is 40°C to 70°C; and the reaction time is 12 to 24 hours. The protective gas is preferably N2.
8. The preparation method according to claim 6, characterized in that: Step (5) is to first disperse the metal ion source material in an organic solvent to obtain a metal ion solution, and then soak the product obtained in step (4) in the metal ion solution for 12 to 24 hours; wherein the concentration of the metal ion solution is 0.5M to 1M; The metal ion source material is anhydrous cupric acetate, zinc chloride, ferric chloride, ferrous chloride or cupric chloride.
9. Use of the medical magnesium-based metal material with a biocatalytic composite coating as claimed in any one of claims 1 to 5 in the preparation of medical implant materials.
Citation Information
Patent Citations
Magnesium-based multifunctional composite active coating as well as preparation method and application thereof
CN114191610A
Application of pH-responsive fluorescent MOFs composites in intelligent anti-corrosion coating materials
CN116376402B